2006
DOI: 10.4172/plastic-surgery.1000487
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of a glomus tumour: A case report

Abstract: A 46-year-old man presented with an extremely painful, 1 cm, mobile, nodular mass located on the medial side of his right elbow. Symptoms failed to respond to conservative treatment. Ultrasound and Doppler flow imaging revealed a well-defined, round hypoechoic mass. Under local anesthesia, the mass was resected and the wound closed without complication. Final pathology diagnosed the lesion as a glomus tumour, solid type. Histology staining showed the tumour cells were positive for antibodies to vimentin and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Most of the cases reported in the literature exhibit Doppler findings similar to those detected in our series, although only a minority of imaging articles illustrate the color Doppler findings, 2,[4][5][6][7][8]18,20,23,25,28,[33][34][35] and only three of them 18,25,35 included the spectral Doppler findings. EDGTs are usually vascularized, although to a variable degree, and are not necessarily hypervascular.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Most of the cases reported in the literature exhibit Doppler findings similar to those detected in our series, although only a minority of imaging articles illustrate the color Doppler findings, 2,[4][5][6][7][8]18,20,23,25,28,[33][34][35] and only three of them 18,25,35 included the spectral Doppler findings. EDGTs are usually vascularized, although to a variable degree, and are not necessarily hypervascular.…”
Section: Discussionsupporting
confidence: 70%
“…[1][2][3][4]7,[10][11][12][13][14][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Additionally, only a minority of these articles include a description of the sonography findings. 2,4,12,13,20,[22][23][24][25]27,29,30,33,34 The three largest series published that included a description of the sonography findings collected 3, 6 4, 35 and 9 18 cases of EDGT, respectively. Glazebrook et al 23 reported the sonography findings in a patients with 4 EDGTs of the leg, 2 subcutaneous and 2 intramuscular, ranging in size from 7 to 52 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first case report of a glomus tumour misdiagnosed as persistent olecranon bursitis. Other reports have described glomus tumours in the forearm [15], medial elbow resulting in medial cutaneous nerve of the forearm symptoms [18] and ulnar nerve symptoms [13]. The initial symptom of a painful swelling was nonspecific and was originally diagnosed as an olecranon bursitis as a result of its location.…”
Section: Discussionmentioning
confidence: 99%